Global Geopotential Model (GGM) Assessmment For Coastal Erosion Study Using Global Navigation Satellite Systems (GNSS) Levelling in Terengganu. - Lau, Tai Wei; Nik Husin, Nur Sharmiza; Mohd Alawi, Aishah HUmaira'; Nornajihah Mohammad Yazid, (Multidisciplinary Applied Research and Innovation, 2024)
GNSS levelling can be used to define the high accuracy geoid based on geodetic, gravimetric, and astrogeodetic approaches. The aim of this study is verify the global geopotential model (GGM) with Global Navigation Satellite System (GNSS) levelling data in order to verify the global model with ground truth data in Terengganu. Hence, the Global Geopotential Model (GGM) model are selected based on satellite-only and combined-model in year 2018 through 2022. Next, the root mean square error (RMSE) is computed for each comparison in order to access the accuracy of each model. The findings found that, ITSG-Grace2018s represents the lowest RMSE value, 0.2190m. Hence, the findings found that ITSG-Grace2018s represents the best fit GGM model with ground truth data in Terengganu. Thus, the local geoid height can be determined accurately in Terengganu using the most precise GGM model.